[PP.34.34]: PROGNOSTIC VALUE OF ON-ADMISSION BLOOD PRESSURE IN ISCHEMIC STROKE. (June 2015) - Brescacin>, L.>; Alonzo, C.; Zurru, M.C.; Pigretti, S.; Camera, L.; Cristiano, E.; Waisman, G.
Abstract : Objective: Patients with acute stroke are often found to have high blood pressure (BP) at hospital admission, and previous studies have shown that higher values are related with worse outcomes. We aim to evaluate the relationship between on-admission BP and 30-day disability, recurrence and mortality. Design and method: Acute ischemic stroke patients were prospectively included in PROTEGE-ACV, a multidisciplinary secondary stroke prevention program. Demographic data and vascular risk factor (VRF) profile and control were prospectively evaluated in the acute-phase and one month after stroke. Patients with transit ischemic attack, unusual mechanism of stroke (TOAST 4) and those with incomplete data were excluded. For the purpose of the analysis, 30-day stroke outcomes (recurrence, mortality and functional status by Barthel index and m-Rankin) were analyzed according to admission SBP, DBP and PP quartiles. Results: 897 ischemic stroke patients (mean age 76 ± 11 years, 60% females) were included between December 2006 and December 2013. Main VRF were hypertension (82%), dyslipidemia (65%), diabetes (14%), metabolic syndrome (39%), smoking (35%) and atrial fibrillation (17%); 75% of patients were receiving antihypertensives, 34% statins, 40% antiplatelets and 10% anticoagulants in the year before. Data on 30-day disability, recurrence and mortality are shown in the table. Figure. No caption available. Conclusions: In our cohort higher on-admission SBP and DBP are related with post-stroke disability but not with early recurrence and mortality. Pulse pressure, a pulsatile component of BP that reflects arterial stiffness and early wave reflections, was the only hemodynamic variable related with hard outcomes.